2013
DOI: 10.1111/jbg.12057
|View full text |Cite
|
Sign up to set email alerts
|

MyoD and Myf6 gene expression patterns in skeletal muscle during embryonic and posthatch development in the domestic duck (Anas platyrhynchos domestica)

Abstract: The MyoD and Myf6 genes, which are muscle regulatory factors (MRFs), play major roles in muscle growth and development and initiate muscle fibre formation via the regulation of muscle-specific gene translation. Therefore, MyoD and Myf6 are potential candidate genes for meat production traits in animals and poultry. The objective of this study was to evaluate MyoD and Myf6 gene expression patterns in the skeletal muscle during early developmental stage of ducks. Gene expression levels were detected using the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Genes controlling craniofacial muscle patterning are poorly characterised; however, muscle determination factors (e.g., myod , myf6 [ Li et al, 2014 ]) appeared unaffected in oil-exposed haddock. Nevertheless, expression levels were significantly reduced for genes involved in the terminal differentiation of skeletal muscle cells, including several myosin heavy chain genes ( myh ) ( Figure 7B , Supplementary file 1J ).…”
Section: Resultsmentioning
confidence: 99%
“…Genes controlling craniofacial muscle patterning are poorly characterised; however, muscle determination factors (e.g., myod , myf6 [ Li et al, 2014 ]) appeared unaffected in oil-exposed haddock. Nevertheless, expression levels were significantly reduced for genes involved in the terminal differentiation of skeletal muscle cells, including several myosin heavy chain genes ( myh ) ( Figure 7B , Supplementary file 1J ).…”
Section: Resultsmentioning
confidence: 99%
“…The identified DEGs are associated with normal physiological cell processes, such as metabolic pathways, endocytosis, and translation as well as muscle development pathways, including cell differentiation, positive regulation of cell proliferation, and Wnt signaling pathway. Many DEGs, such as MSTN, TMEM8C, MYF6, and SOX4, reportedly regulate myogenesis and were enriched in important pathways (Abmayr and Pavlath, 2012;Jang et al, 2013;Li et al, 2014;Retamales et al, 2015;Zhang et al, 2015;Millay et al, 2016). We also found that FOXO1 was a DEG after H19 knockdown.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, differences in MyoD and MyoG expression among strains could be attributed to long-term genetic selection or type of production (Zhang et al 2018). Other factors such as physiological and environmental conditions (Yin et al 2014), different genetic origins, skeletal muscle contents (Li et al 2014), and polymorphisms (Zhu et al 2010) could also be involved in gene expression differences among strains. Results of MSTN expression in the present study are in agreement with the findings of several previous studies that showed a negative association between MSTN levels and increase in size and number of skeletal muscle fibres or muscle mass (Grobet et al 1997;Kambadur et al 1997;Lee 2004), and the results of final body weights of the four strains in the current study support these findings.…”
Section: Discussionmentioning
confidence: 99%